(3GdbGfhf GdeSYhOis - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3GdeSYhO Hf SYO HGddg hGfaQO HJCjjOg EjGg Yf GdCTcGd hGdCTHGg s
(3BNQgG (B:s
(3hEP HdZJ gPG GdehVY ef GdcJGH abO Bf GNJJGeg HGdMeO ddg GdhGMO GdYed Pi Gdef hGdWhd s
(3ajgG cKjQ ef GdLOGhd hGdQShe GdgfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B475 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B79 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdadcs